Historical adventure. - Twain, Mark, 1835-1910; Verne, Jules, 1828-1905; Hope, Anthony, 1863-1933 (Bank Street graphic novels, 2007)
Presents graphic novel adaptations of Mark Twain's tale about a nineteenth-century American transported to sixth-century England; Jules Verne's story about a Victorian gentleman who sets out to win a bet by circumnavigating the globe in eighty days or less; and Anthony Hope's story in which an English ne'er-do-well falls into intrigue involving the new king of Ruritania, a distant relative with whom he shares an uncanny likeness.